Pengaruh Belanja Pembangunan Infrastruktur Terhadap Pertumbuhan Ekonomi Provinsi Kalimantan Utara - Sari, Yundi Kurnia Indah; A, Aslan; Y, Yuliansyah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Infrastructure development is one of the main requirements for achieving rapid and sustainable economic growth. This research aims to: (1) To analyze the amount of spending on economic infrastructure development and identify and evaluate the amount of spending on economic infrastructure development that has been allocated in North Kalimantan and (2) To find out how infrastructure spending influences economic growth in North Kalimantan Province. Based on the results of the analysis using simple regression, namely; (1) Infrastructure development in the road, transportation and electricity sectors has a positive impact on social aspects and human development, thus infrastructure development in North Kalimantan Province is not just physical development but is also an investment strategy in economic growth and community welfare. (2) Infrastructure development has a positive and significant effect on economic growth in North Kalimantan province. This means that an increase or decrease in infrastructure development has a direct effect on the increase or decrease in economic growth in North Kalimantan Province.